Leveraging Informal Learning Pedagogies to Empower Coastal Communities for Disaster Preparedness - Pradhananga, Piyush; Elawady, Amal; ElZomor, Mohamed (Frontiers in Built Environment, 2022)
With the increasing frequency and intensity of hurricanes, people and communities within hurricane-prone zones are often overwhelmed and lack effective preparedness in terms of social connectivity critical for making proactive decisions to survive anticipated disasters. Disaster management agencies traditionally share preparedness guidelines through formal educational and other public media channels (such as academic institutions, articles, and the Federal Emergency Management Agency, etc.) only. However, such formal modalities seldom consider the socio-economic status, cultural background, diversity, and education level of communities. Consequently, vulnerable communities are challenged by poor inclusive accessibility, lack of receptiveness, and responsiveness. An Informal Learning Pedagogy (ILP) for hurricane preparedness can be a practical solution to disseminate knowledge on preparedness and hurricane impacts at the community level through nurturing enthusiasm to learn from one another within the community setting, which causes ripple effects that are more profound within a diverse community. This approach would effectively support educating more people about hurricane preparedness. The main objectives of this study are: 1) to assess the hurricane preparedness awareness of people living in a hurricane-prone coastal community in South Florida, United States; 2) to investigate the applicability of adopting novel ILP mechanisms for a disaster-prone community and; 3) analyze and plan for the development of online community-centered hurricane preparedness training with a primary focus on preparedness, warning, evacuation, and early recovery. Developing training modules focused on disaster preparedness through informal learning environments depends on incorporating actual community requirements, which reflect audience-centered needs as part of enhancing the resilience capacity of coastal communities. As such, in this study, an online questionnaire survey focusing on the validation of the research hypothesis was designed and conducted among South Florida residents. The survey data results indicated that participation in disaster-preparedness training through informal modalities highly depends on the length of an individual’s stay in a disaster-prone zone, anticipated benefits of disaster education, and the availability of online training. This research study contributes to the disaster preparedness and response bodies of knowledge by identifying informal ways of communicating hazard preparedness knowledge to advance the resilience capacities in disaster-prone communities.